Laparoscopic bile duct resection with lymph node dissection for gallbladder cancer diagnosed after laparoscopic cholecystectomy. (December 2020) - Han, Sunjong; Yoon, Yoo-Seok; Han, Ho-Seong; Lee, Jun Suh
Abstract: Introduction: Laparoscopic reoperation of postoperatively diagnosed gallbladder cancer is a technically challenging procedure due to inflammatory adhesion or fibrosis around the hepatoduodenal ligament and gallbladder bed [1, 2]. Here we describe a technique for laparoscopic bile duct resection with lymph node dissection in a patient with cystic duct cancer diagnosed after laparoscopic cholecystectomy. Video: A 73-year-old woman presented with postoperatively diagnosed gallbladder cancer. She underwent laparoscopic cholecystectomy to treat symptomatic gallbladder stones at another hospital, 2 months earlier. Postoperative pathology revealed a 0.9 × 0.7 cm, T2 lesion of adenosquamous carcinoma located at the cystic duct. The cystic duct margin showed high-grade dysplasia. We planned to perform laparoscopic bile duct resection with lymph node dissection. After adhesiolysis to expose the hepatoduodenal ligament, the lymph nodes were dissected around the retropancreatic area, hepatoduodenal ligament, and common hepatic artery in an en bloc fashion. Combined segmental resection of the bile duct, including the fibrotic scar around the cystic duct stump, was completed with negative resection margins. Retrocolic choledochojejunostomy and side-to-side jejunojejunostomy were then performed intracorporeally. Results: The operation time was 195 minutes and the estimated intraoperative blood loss was minimal. The postoperative pathologic report revealed no residual tumor tissue and negative resection margins. Lymph node metastasis was found in one of eight retrieved lymph nodes. The patient was discharged on postoperative day 4 with no postoperative complications. Conclusion.Laparoscopic radical surgery involving bile duct resection and lymph node dissection can be safely performed in patients with postoperatively diagnosed gallbladder cancer. Highlights: Postoperative diagnosis of gallbladder cancer is increasing due to greater use of laparoscopic cholecystectomy. Laparoscopic reoperation is technically challenging due to postoperative inflammatory adhesion or fibrosis. This video shows a laparoscopic surgical technique for cystic duct cancer diagnosed after laparoscopic cholecystectomy.